Age constraint for the Moreno Hill Formation (Zuni Basin) by CA-TIMS and LA-ICP-MS detrital zircon geochronology - Charl D. Cilliers; Ryan T. Tucker; James L. Crowley; Lindsay E. Zanno (PeerJ, 2021)
The “mid-Cretaceous” (~125–80 Ma) was punctuated by major plate-tectonic upheavals resulting in widespread volcanism, mountain-building, eustatic sea-level changes, and climatic shifts that together had a profound impact on terrestrial biotic assemblages. Paleontological evidence suggests terrestrial ecosystems underwent a major restructuring during this interval, yet the pace and pattern are poorly constrained. Current impediments to piecing together the geologic and biological history of the “mid-Cretaceous” include a relative paucity of terrestrial outcrop stemming from this time interval, coupled with a historical understudy of fragmentary strata. In the Western Interior of North America, sedimentary strata of the Turonian–Santonian stages are emerging as key sources of data for refining the timing of ecosystem transformation during the transition from the late-Early to early-Late Cretaceous. In particular, the Moreno Hill Formation (Zuni Basin, New Mexico) is especially important for detailing the timing of the rise of iconic Late Cretaceous vertebrate faunas. This study presents the first systematic geochronological framework for key strata within the Moreno Hill Formation. Based on the double-dating of (U-Pb) detrital zircons, via CA-TIMS and LA-ICP-MS, we interpret two distinct depositional phases of the Moreno Hill Formation (initial deposition after 90.9 Ma (middle Turonian) and subsequent deposition after 88.6 Ma (early Coniacian)), younger than previously postulated based on correlations with marine biostratigraphy. Sediment and the co-occurring youthful subset of zircons are sourced from the southwestern Cordilleran Arc and Mogollon Highlands, which fed into the landward portion of the Gallup Delta (the Moreno Hill Formation) via northeasterly flowing channel complexes. This work greatly strengthens linkages to other early Late Cretaceous strata across the Western Interior.